Taskshifting: translating theory into practice to build a community based mental health care system in rural Haiti. Issue 3 (November 2015) - Legha, Rupinder; Eustache, Eddy; Therosme, Tatiana; Boyd, Kate; Reginald, Fils-Aime; Hilaire, Gertruna; Daimyo, Shin; Jerome, Gregory; Verdeli, Helen; Raviola, Giuseppe
Abstract : In 2012, Zanmi Lasante, a Haitian nonprofit organisation, along with its sister organisation, Partners in Health, developed a mental health plan intended to go beyond the immediate post earthquake context by building capacity for mental health and psychosocial services within primary care services at 11 Zanmi Lasante sites throughout Haiti's Central Plateau and Artibonite regions. This paper describes laying the foundation for a community based, mental health care system through the articulation of a 'depression care pathway', in which patients are identified and treated within the community, but referred to clinics and more specialised care when required. We emphasise taskshifting clinical, service delivery, systems building, and quality improvement responsibilities to psychologists, the central players in the Zanmi Lasante mental health model. By describing challenges and providing practical, implementable solutions, we highlight how this fundamental theory in global mental health translates into daily practice in a health care setting with limited biomedical services, clinical training and human resources. We also provide recommendations for optimising taskshifting when initiating community based mental health services in similar resource limited settings.